2004
DOI: 10.1021/es040029t
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Sediment-Bound Bioavailable Polychlorobiphenyls by Benthivorous Carp (Cyprinus carpio)

Abstract: It is unclear whether accumulation of sediment-bound chemicals in benthivorous fish depends on the degree of sequestration in the sediment like it does for invertebrates. Here, we report on the potential of slow and fast desorbing sediment-bound polychlorobiphenyl (PCB) fractions for accumulation in carp (Cyprinus carpio) in lake enclosures treated with different nutrient doses. Routes of PCB uptake were quantitatively evaluated for 15 PCBs (log Kow range 5.6-7.8) using model analysis. Fast-desorbing PCB fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 37 publications
3
52
1
Order By: Relevance
“…This result for nitroaromatic compounds is in contrast with results obtained during studies of similar organic contaminants including PAHs, PCBs and other persistent organic pollutants, where it was reported that direct contact with sediment surfaces resulted in uptake by benthic fish (Stein et al, 1984;Hellou et al, 1994Hellou et al, , 1995Smith et al, 1996;Moermond et al, 2004;Fragoso et al, 2006). The body residue of benzo(a)pyrene via dermal contact, evaluated using anesthetized catfish (Ictalurus punctatus) placed directly on spiked sediment, was several times higher than in fish not in direct contact with the sediment (Smith et al 1996).…”
Section: Bioaccumulation and Toxicitycontrasting
confidence: 81%
“…This result for nitroaromatic compounds is in contrast with results obtained during studies of similar organic contaminants including PAHs, PCBs and other persistent organic pollutants, where it was reported that direct contact with sediment surfaces resulted in uptake by benthic fish (Stein et al, 1984;Hellou et al, 1994Hellou et al, , 1995Smith et al, 1996;Moermond et al, 2004;Fragoso et al, 2006). The body residue of benzo(a)pyrene via dermal contact, evaluated using anesthetized catfish (Ictalurus punctatus) placed directly on spiked sediment, was several times higher than in fish not in direct contact with the sediment (Smith et al 1996).…”
Section: Bioaccumulation and Toxicitycontrasting
confidence: 81%
“…Smallmouth bass has previously been observed to accumulate higher levels of persistent organohalogen compounds and mercury than other organisms due to trophic position (Kwon et al, 2006;Sethajintanin et al, 2004), but only recently has the importance of the direct link between benthic uptake and predatory fish been observed (Carlson et al, 2010;Hogan et al, 2007). Prior to the invasion of the round goby, the lack of a benthic link allowed for the sequestration of such persistent compounds to benthic organisms (Moermond et al, 2004). The more rapid rate of change simulated for the zebra mussel is indicative of benthic isolation and implies that the round goby is not as efficient as the zebra mussel with respect to PBDE uptake or that the dietary assumptions made for the zebra mussel are too drastic and must be revised.…”
Section: Symbolmentioning
confidence: 99%
“…It has been argued that direct uptake from water via the gills is predominant in small fish individuals e.g., early life stages and for low LogK OW PCB congeners, whereas uptake from food dominates in adult fish and for higher chlorinated PCBs. 23,41,42 One-year-old Golden Orfe feeds mainly on zooplankton, both in pelagic and benthic habitats, and thus is subjected to PCB uptake from both food and water.…”
Section: Environmental Science and Technologymentioning
confidence: 99%